Costs and quality of life in multiple sclerosis: A cross-sectional observational study in Germany - Gisela Kobelt; Peter Lindgren; Antje Smala; Bengt Jönsson (Stockholm School of Economics, The Economic Research Institute (EFI), 2000)
We performed a cross-sectional, bottom-up observational study of resource consumption and quality of life of patients with multiple sclerosis (MS) in Germany. Six centers participated in the study. Patients were asked to complete a questionnaire, and a total of 737 patients returned the questionnaire (the answer rate being 66%). The questionnaire provided information on all resource consumption, medical and non-medical, work absence and informal care related to their MS. Simultaneously, medical charts were also abstracted for a sub sample of 202 patients. For this sub sample, disease scores (Expanded Disability Status Scale, EDSS) were available from the study centers. For the remainder, disease scores were assigned using a matrix of disease (mobility) descriptions and EDSS scores. Mean total cost per patient and year was 65,400 DM, adjusted for usage of interferons, which was higher in this sample than the current average usage in Germany. When this cost is extrapolated to an estimated patient population of 120,000, total costs to society are estimated at 7.85 billion DM. Direct costs represented 57.5%, informal care accounted for 12.1% and indirect costs amounted to 42.5%. An estimated 24,800 DM per patient or 38% of total costs are paid for by public payers. Intangible costs were estimated 16,650 DM per patient and year. The mean age of the cohort was 42 years (disease onset 33), the mean utility measured with EQ-5D was 0.552 (0.919 to -0.429), and the mean EDSS score 4.4 (1.0 to 9.5). All costs (direct, informal care, indirect) increased with increasing EDSS scores, while utilities decreased.
Keywords: D61; H42; H51; H55; I18; 330; multiple sclerosis; cost-of-illness; quality of life; EDSS; utility; Krankheit; Kosten; Lebensqualität; Statistischer Test; Deutschland